2022
DOI: 10.22141/2224-1485.1.45.2016.74137
|View full text |Cite
|
Sign up to set email alerts
|

Диабетическая Кардиальная Автономная Нейропатия: Каковы Перспективы В Лечении?

Abstract: Резюме. Кардиальная автономная нейропатия (КАН) является серьезным и частым осложнением са

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
4

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 108 publications
0
18
0
4
Order By: Relevance
“…A major complication observed in T2DM patients is cardiovascular autonomic neuropathy (CAN), a severe clinical problem accounting for resting tachycardia, orthostatic hypotension, decreased heart rate variability, cardiorespiratory instability, silent myocardial infarction and, importantly, increased mortality risk. 129,130 The earliest manifestations of autonomic neuropathy in T2DM patients tend to be associated with parasympathetic denervation. By contrast, the sympathetic system is affected only at an advanced stage of the disease.…”
Section: Exercise Training For Patients With T2dm and Cardiovascular mentioning
confidence: 99%
“…A major complication observed in T2DM patients is cardiovascular autonomic neuropathy (CAN), a severe clinical problem accounting for resting tachycardia, orthostatic hypotension, decreased heart rate variability, cardiorespiratory instability, silent myocardial infarction and, importantly, increased mortality risk. 129,130 The earliest manifestations of autonomic neuropathy in T2DM patients tend to be associated with parasympathetic denervation. By contrast, the sympathetic system is affected only at an advanced stage of the disease.…”
Section: Exercise Training For Patients With T2dm and Cardiovascular mentioning
confidence: 99%
“…Ризик виникнення СН за наявності ЦД-2 зумовлений поєднанням діабетичної кардіоваскулярної автономної нейропатії (КАН), кардіоміопатії, ІХС та АГ [1][2][3]. КАН -одна з найбільш прогностично несприятливих і клінічно значущих форм автономної нейропатії, що діагностується незадовільно, може спричинювати ішемію вінцевих судин, «німий» інфаркт міокарда (ІМ); навіть доклінічна стадія КАН збільшує, а клінічна значно збільшує ймовірність синдрому раптової смерті; може бути передвісником виникнення гострих порушень мозкового кровотоку [1,4,5]. Отже, дослідження й з'ясування патогенезу КАН, рання діагностика, пошук шляхів і способів ефективного лікування є одними з пріоритетних завдань сучасної діабетології.…”
Section: вступunclassified
“…Хронічна гіперглікемія, ГІ та/або ІР супроводжуються порушеннями ліпідного обміну, і їх вираженість може корелювати зі ступенем тяжкості ДЛП. Вважається, що власне ГІ є рушійною силою активації патофізіологічних процесів формування та/або наростання тяжкості ССЗ у хворих на ЦД-2 [4][5][6].…”
Section: вступunclassified
“…Animal models of diabetes have revealed that aminoguanidine (AG), a known inducible nitric oxide synthase (iNOS) inhibitor, prevents diabetes-associated cardiovascular deterioration, nephropathy, retinopathy and neuropathy (7)(8)(9). In addition, it has been demonstrated that AG inhibits the formation of AGEs by interacting with and quenching dicarbonyl compounds (10), protecting against myocardial contractile dysfunction (11).…”
Section: Introductionmentioning
confidence: 99%